2017
DOI: 10.1093/ve/vex010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the evolution and spread of chikungunya virus in the Americas using complete genome sequences

Abstract: Local transmission of chikungunya virus (CHIKV) was first detected in the Americas in December 2013, after which it spread rapidly throughout the Caribbean islands and American mainland, causing a major chikungunya fever epidemic. Previous phylogenetic analysis of CHIKV from a limited number of countries in the Americas suggests that an Asian genotype strain was responsible, except in Brazil where both Asian and East/Central/South African (ECSA) lineage strains were detected. In this study, we sequenced thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
48
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 46 publications
13
48
1
8
Order By: Relevance
“…This population-specific competence is similar to what has been reported in other studies, 16,20 yet our results suggest that CHIKV competence is more dependent on mosquito population than DENV competence, perhaps reflecting the shorter evolutionary history of this virus in the region. 36,37 Whereas this suggests that further adaptive evolution of CHIKV in the region could enhance transmission, 38 an important caveat of these studies is that a single CHIKV isolate was used and other viral genotypes could be inherently more transmissible. 39 Although previous findings of increased temperatures resulting in decreased extrinsic incubation and increased competence are generally supported by our data, 6,7,9 results also demonstrate that fluctuations in temperature will have both virus species-and population-specific effects on competence.…”
Section: Discussionmentioning
confidence: 99%
“…This population-specific competence is similar to what has been reported in other studies, 16,20 yet our results suggest that CHIKV competence is more dependent on mosquito population than DENV competence, perhaps reflecting the shorter evolutionary history of this virus in the region. 36,37 Whereas this suggests that further adaptive evolution of CHIKV in the region could enhance transmission, 38 an important caveat of these studies is that a single CHIKV isolate was used and other viral genotypes could be inherently more transmissible. 39 Although previous findings of increased temperatures resulting in decreased extrinsic incubation and increased competence are generally supported by our data, 6,7,9 results also demonstrate that fluctuations in temperature will have both virus species-and population-specific effects on competence.…”
Section: Discussionmentioning
confidence: 99%
“…Lineage-specific clinical presentations have been recently highlighted by a recent index cluster study which showed that 82% of CHIKV infections caused by the ECSA lineage are symptomatic, in comparison to only 52% of symptomatic infections caused by the Asian genotype [54]. While the Asian lineage seems to have circulated cryptically for 9 months before its first detection in the Caribbean [3], the faster detection of the ECSA lineage in Brazil could at least in part be a consequence of a higher rate of symptomatic to asymptomatic infections of the ECSA lineage circulating in Brazil. The time lag between the phylogenetic estimate of the date of introduction of a virus lineage and the date of the first confirmed case in a given region, enables us to identify surveillance gaps between the arrival and discovery of a virus in that region [69].…”
Section: Discussionmentioning
confidence: 99%
“…Доказано, в частности, что мутации E1-K211E и E2-V264A повышают инфекционность вируса в отношении Ae. aegypti [30,36,40].…”
unclassified
“…Высказывается мнение, что это способствовало дальнейшему расширению распространения восточно-центрально-южноафриканской линии вируса и привело к возможности реализации непродолжительной по времени локальной передачи CHIKV на новых для него «северных» территориях, в частности, в регионах Европейского Средиземноморья (побережье Италии, Франции), где плотность популяций Ae. albopictus высока [36].…”
unclassified
See 1 more Smart Citation